PENGEMBANGAN SISTEM ZONASI PADA APLIKASI SAPEDA MADRASAH ALIYAH KABUPATEN PANGKEP MENGGUNAKAN METODE HAVERSINE FORMULA - Muh. Fajri Raharjo; Utomo, Muhammad Nur Yasir; Ramadhani, Ainun Zulkiah (Journal of Informatics and Computer Engineering Research, 2025)
The SAPEDA application in Pangkep Regency currently lacks a feature that allows prospective students to determine the nearest school to their residence. This has led to an inefficient school selection process and unequal distribution of students. The aim of this research is to develop a zoning system for the SAPEDA application at Madrasah Aliyah in Pangkep Regency. The study employs the Haversine Formula in the zoning feature to calculate the distance between students' homes and nearby schools, offering an effective approach to improve the SAPEDA system. This will help prospective students choose the nearest school, reduce transportation costs, and promote equitable access to education. The research procedure includes a literature review, interviews, system design, system development, and testing. Results from a questionnaire based on the TAM (Technology Acceptance Model) show that the system is well-received and positively evaluated by respondents, with an average score of 90.62%, categorized as Excellent. This indicates, that the system has successfully provided benefits, ease of use, and has met users' expectations across various evaluated aspects, resulting in a high level of satisfaction